Water banking in Fergana valley aquifers: a solution to water allocation in the Syrdarya river basin? - Karimov, Akmal A.; Smakhtin, Vladimir U.; Mavlonov, A.; Gracheva, I. (Elsevier, 2010)
The Syrdarya river is an example of a transboundary basin with contradictory water use requirements between its upstream and downstream parts. Since the winter of 1992-93, the operational regime of the upstream Toktogul reservoir on the Naryn river - the main tributary of the Syrdarya - has shifted from irrigation to hydropower generation mode. This significantly increased winter flow and reduced summer flowdownstream of the reservoir. Consequently, excessive winterflowis diverted to the saline depression called Arnasai, while water for summer irrigation is lacking. This study suggests to store the excessive winter flows temporarily in the upstream aquifers of the Fergana valley and to use it subsequently for irrigation in summer. It is estimated that groundwater development for irrigation could be practiced on one-third of the irrigated land of the valley, and conjunctive use of groundwater and canal water on another third; the rest will remain under canal irrigation. This strategy will lower the groundwater table and create aquifer capacity for temporal storage of excessive water?"water banking?. This use of the term is only one of many concepts to which "water banking? or "groundwater banking? is applied. In this paper, the term is applied for temporary storing of river flow in subsurface aquifers. Pilot modeling studies for the Sokh aquifer - one of the 18 aquifers of the Fergana valley - supported that this strategy is a feasible solution for the upstream-downstream issues in the Syrdarya river basin. Field studies of water banking are required to determine the scale of adoption of the proposed strategy for each aquifer of the Fergana valley.